Roles of Islamic Microfinance Institutions in Improving Financial Inclusion in Indonesia: Empirical Evidence from Baitulmaal wa Tamwil - Adhitya Ginanjar; Salina Hj Kassim (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2021)
Abstract. This research aims to investigate the role of Islamic microfinance institutions (IMFIs) in promoting financial inclusion in Indonesia. It takes seven areas, namely, Jakarta, Bogor, Depok, Tangerang, Bekasi, Yogyakarta and Nusa Tenggara Barat as samples. Only managers of the IMFIs are taken as respondents since they are the decision makers and understanding of the mission of the IMFIs. A complete of 481 managers of Baitulmaal Wa Tamwil (BMTs) which administered under the Sharia Cooperative Centre involved in the study. Qualitative method was used in this research for determining the variables in advancing model that developed with two mechanism in the data collection; the first mechanism involved a survey questionnaire, and the second mechanism involved in-depth interview. The findings of this research reveal current issues and challenges in strengthening the role of IMFIs in promoting financial inclusion and highlight recommendations for policy makers to promote financial inclusion. Keywords: Financial Inclusion; Islamic Micro-Finance Institutions; Baitul Maal wa Tamwil, Islamic Finance.Abstrak. Penelitian ini bertujuan untuk mengetahui peran lembaga keuangan mikro Islam (LKMS) dalam mendorong inklusi keuangan di Indonesia. Dibutuhkan tujuh area riset, yakni wilayah Jakarta, Bogor, Depok, Tangerang, Bekasi, Yogyakarta dan Nusa Tenggara Barat sebagai sampel. Hanya manajer LKMS yang diambil sebagai responden karena mereka adalah pengambil keputusan dan memiliki pemahaman yang jelas tentang misi LKMS. Sebanyak 481 pengurus Baitulmaal Wa Tamwil (BMT) di bawah naungan Induksi Koperasi Syariah sebagai sampel. Metode kualitatif digunakan dalam penelitian ini dengan dua mekanisme yang dikembangkan dalam pengumpulan data; mekanisme pertama melibatkan kuesioner survei, dan mekanisme kedua melibatkan wawancara meSndalam. Temuan penelitian ini mengungkapkan isu dan tantangan terkini dalam memperkuat peran LKMS dalam mendorong inklusi keuangan. Hasil ini juga menyoroti beberapa rekomendasi bagi BMT dan pembuat kebijakan untuk mempromosikan inklusi keuangan.Keyword: Keuangan Inklusi; Lembaga Keuangan Mikro Syariah; Baitumaal Wa Tamwil; Keuangan Syariah.